A high entropy material and its preparation method and application

Through mechanochemical synthesis method and modifier adjustment, a high-entropy oxide catalyst was prepared, which solved the problems of poor thermal stability and insufficient adaptability of the existing CuZnAl catalyst, achieved efficient catalytic conversion of CO2 hydrogenation and improved thermal stability, and expanded the application of high-entropy oxides in the catalytic field.

CN116262229BActive Publication Date: 2025-04-22DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111532075.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-15
Publication Date
2025-04-22
Estimated Expiration
2041-12-15

AI Technical Summary

Technical Problem

The existing CuZnAl catalysts have poor thermal stability, complex redox cycles and difficult adaptation to complex working conditions in CO2 hydrogenation reactions, and the high cost and complex preparation process of precious metal catalysts limit their industrial applications.

Method used

By using mechanochemical synthesis method, high entropy oxide catalysts with high crystallinity and uniform bulk morphology are prepared by introducing modifiers such as urea, ammonium bicarbonate or thiourea.

Benefits of technology

It realizes efficient catalytic conversion of CO2 hydrogenation, improves the thermal stability and adaptability of the catalyst, simplifies the preparation process, reduces costs, and expands the application of high-entropy oxides in the catalytic field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003411725630000081
    Figure BDA0003411725630000081
  • Figure HDA0003411725640000011
    Figure HDA0003411725640000011
  • Figure HDA0003411725640000012
    Figure HDA0003411725640000012
Patent Text Reader

Abstract

The present invention discloses a high entropy material and a preparation method and application thereof. The high entropy material comprises an oxide of an active metal element and an oxide of a structurally stable metal element; the active metal element is selected from copper, cobalt and nickel; the structurally stable metal element is selected from zinc and aluminum; the molar contents of the active metal element and the structurally stable metal element are 60% and 40%, respectively. The crystallinity of the high entropy material is 56.7% to 72.3. The preparation method is simple and easy, time-saving, no aqueous solution is required during the preparation process, it is green and environmentally friendly, and has a high yield. The high entropy oxide prepared by the present invention has a uniform block shape and exhibits excellent catalytic performance and stability in the CO2 hydrogenation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high entropy material and a preparation method and application thereof, belonging to the field of inorganic material preparation and application. Background Art

[0002] Since the beginning of the 21st century, fossil energy has been rapidly consumed with the rapid development of industry and the intensification of human activities. In addition to causing various atmospheric pollution problems, the large-scale emission of the most important greenhouse gas carbon dioxide (CO2) has attracted widespread attention around the world and caused phenomena such as global warming, acid rain and glacier melting. Based on this, various countries have adopted strategic goals for carbon emission reduction and formulated a timetable for carbon neutrality. In addition to the widely adopted CO2 capture and storage technology, the conversion of CO2 into hydrocarbons such as methanol not only has important scientific significance, but also has broad application prospects. Cu-based catalysts are important CO2 hydrogenation catalysts, among which CuZnAl catalysts have also been industrially applied. However, the Cu state of this series of catalysts is more complicated during the reaction process, there are more types of redox cycles in the corresponding catalysts, and the thermal stability is poor. It cannot adapt to complex working conditions and expand its field. Although there are also reports on the research of precious metal efficient CO2 hydrogenation catalysts, their high cost, complex preparation process and the easy sintering of active sites at high temperatures also limit their application in the industrial field. Therefore, it is particularly important to develop efficient Cu-based CO2 hydrogenation catalysts.

[0003] High entropy materials are a new type of materials composed of multiple principal components in equimolar or nearly equimolar ratios. Due to its unique properties compared to traditional single principal component materials, it has attracted widespread attention from researchers in the field of inorganic non-metals in recent years. Further extended to multi-component oxides, when it is composed of five or more oxides in equimolar or nearly equimolar ratios, this type of oxide is called high entropy oxide. This oxide breaks the design concept of traditional doped oxides. On the one hand, due to the high configuration entropy of the system, it is easy to form simple solid solution structures such as rock salt, fluorite, spinel or perovskite; on the other hand, the principal components tend to be arranged in a disordered manner, and its chemical composition is in a disordered state, resulting in various performances that are different from traditional doped oxides. High entropy oxides embody "collective characteristics" due to multiple principal components. Since their advent, they have attracted the interest of many researchers due to their unique properties, such as extremely high thermal stability, unique magnetic properties, huge dielectric properties and excellent catalytic properties. At present, the main preparation methods of high entropy are: co-precipitation method, solution combustion method, wet synthesis, etc. Among them, coprecipitation method and solution combustion method are the most common methods for synthesizing hydrotalcite. However, these two methods have the disadvantages of many operation steps, high energy consumption, low yield, and difficulty in regulation. Summary of the invention

[0004] The present invention overcomes the above shortcomings and proposes a green and simple method for preparing and modifying high entropy oxides. Active metal sources and structurally stable metal sources are used as raw materials, and the physicochemical properties of high entropy oxides are improved by introducing modifiers. This method can not only obtain a rock salt structure with high crystallinity, but also present a uniform block. The present invention provides a reference for the simple and green preparation and modification of high entropy oxides, and has broad and far-reaching use value. Based on excellent physicochemical properties, the prepared magnesium aluminum hydrotalcite has excellent CO2 hydrogenation catalytic conversion effect, further expanding the application field of high entropy oxides.

[0005] According to one aspect of the present application, a high entropy material is provided, comprising an oxide of an active metal element and an oxide of a structurally stable metal element;

[0006] The active metal element is selected from copper, cobalt and nickel;

[0007] The structural stabilizing metal element is selected from zinc and aluminum;

[0008] The molar ratio of the active metal element to the structurally stable metal element is 6:4;

[0009] The crystallinity of the high entropy material is 56.7% to 72.3%.

[0010] According to another aspect of the present application, a method for preparing the above-mentioned high entropy material is provided, comprising at least the following steps:

[0011] The active metal element precursor and the structurally stable metal element precursor are mixed with a modifier and subjected to high-temperature treatment to obtain the high entropy material.

[0012] The active metal element precursor and the structurally stable metal element precursor are selected from at least one of nitrates, sulfates or chlorides of the corresponding metal elements;

[0013] The modifier is selected from at least one of urea, ammonium bicarbonate or thiourea;

[0014] The molar ratio of the active metal element precursor to the structurally stable metal element precursor is 1:1;

[0015] The molar ratio of the total molar amount of the active metal element precursor and the structurally stable metal element precursor to the molar amount of the modifier is 0.5-2.

[0016] The mixing includes ball milling I;

[0017] The ball milling time of the active metal element precursor and the structurally stable metal element precursor is 20 to 40 minutes.

[0018] The temperature of the high temperature treatment is 700-1000°C;

[0019] The high temperature treatment time is 2 to 6 hours.

[0020] The active metal element precursor and the structurally stable metal element precursor are subjected to ball milling II with a modifier;

[0021] The time of ball milling II is 15 to 30 minutes.

[0022] Specifically, the method comprises the following steps: mechanically mixing an active metal source, a structurally stable metal source and a modifier, performing a curing reaction, and then obtaining a high entropy oxide catalyst by high temperature calcination. This method utilizes a mechanochemical synthesis method, achieves uniform dispersion between metals by grinding, and fine-tunes the microenvironment of the crystallization process under high temperature conditions by adding a modifier. On the one hand, the added modifier generates gas under high temperature conditions to act as a pore-forming agent, and on the other hand, improves the lattice oxygen properties of the metal oxide surface by creating a local high-pressure environment. This method is simple and easy to implement, takes a short time, does not require an aqueous solution during the preparation process, is green and environmentally friendly, and has a high yield.

[0023] Optionally, the high entropy oxide has a crystallinity of 56.7% to 72.3%.

[0024] Optionally, the yield of the high entropy oxide is 92% to 98%.

[0025] The active metal source includes three metals: Cu, Co, and Ni;

[0026] The structure-stabilizing metal source includes Zn and Al;

[0027] The modifier is one of urea, ammonium bicarbonate or thiourea;

[0028] Each active metal and each structure stabilizing metal are equimolar;

[0029] The ratio of the total molar number of the active metal and the structural stabilizing metal to the molar number of the modifier is 0.5-2;

[0030] The active metal and structure-stable metal salt is one of nitrate, sulfate or chloride;

[0031] Optionally, the specific step of mechanical mixing includes: after ball milling the active metal source and the stabilizing metal source for the first time, adding the modifier and performing a second ball milling;

[0032] The first ball milling time is 15 to 30 minutes;

[0033] The second ball milling time is 20 to 40 minutes.

[0034] Optionally, the curing reaction temperature is 700-1000° C. and the time is 2-6 hours.

[0035] Optionally, the curing reaction temperature may be independently selected from 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C;

[0036] Optionally, the curing time may be independently selected from 2h, 3h, 4h, 5h, 6h.

[0037] According to another aspect of the present application, a catalyst is provided, wherein the catalyst comprises the above-mentioned high entropy material or the high entropy material prepared by the above-mentioned preparation method.

[0038] According to another aspect of the present application, a method for hydrogenating carbon dioxide is provided, comprising at least the following steps:

[0039] The mixed gas containing carbon dioxide and hydrogen is contacted with a catalyst to react and obtain a product containing carbon monoxide, methane or methanol;

[0040] The catalyst is selected from the above-mentioned catalysts.

[0041] In the mixed gas, the volume ratio of carbon dioxide to hydrogen is 4:1;

[0042] The flow rate of the mixed gas is 20 mL / min to 50 mL / min; optionally, the flow rate of the mixed gas is 20 mL / min, 30 mL / min, 40 mL / min, or 50 mL / min.

[0043] The mass of the catalyst is 0.2-0.5 g. Optionally, the mass of the catalyst is 0.2 g, 0.3 g, 0.4 g, or 0.5 g.

[0044] The reaction temperature is 200-550°C. The heating rate is 3°C / min;

[0045] Alternatively, the reaction temperature may be independently selected from 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C.

[0046] The beneficial effects of this application include:

[0047] 1) The high entropy oxide prepared by the present invention is synthesized by a mechanochemical method, and the preparation process does not require a solvent, the process is simple, the yield is high, and it is conducive to large-scale preparation.

[0048] 2) The present invention achieves the regulation and improvement of the physical and chemical properties of high entropy oxides simply by adding a modifier.

[0049] 3) The high entropy oxide prepared by the present invention has good structure, high crystallinity and uniform morphology, and can achieve simultaneous improvement of CO2 hydrogenation catalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0051] Figure 1 XRD spectra of high entropy oxides prepared in Examples 2 and 3 of the present invention;

[0052] Figure 2 a and b are SEM images of high entropy oxide prepared in Example 4 of the present invention;

[0053] Figure 3 1 and 2 are He-TPD curves of the high entropy oxides prepared in Comparative Example 1 and Example 3 of the present invention. DETAILED DESCRIPTION

[0054] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0055] Example 1

[0056] 0.4832g of copper nitrate hexahydrate, 0.5820g of cobalt nitrate hexahydrate, 0.5816g of nickel nitrate hexahydrate, 0.5950g of zinc nitrate hexahydrate and 0.7464g of aluminum nitrate hexahydrate were weighed respectively, and then transferred to an agate jar for ball milling for 20 minutes. After the mechanical mixing is completed, 0.360g of urea is added and the ball milling is continued for 30 minutes. The ball-milled mixture is then placed in a crucible and transferred to a muffle furnace and reacted at 900°C for 3 hours. After the reaction is completed, it is cooled to room temperature to obtain a high entropy oxide, which is recorded as catalyst A.

[0057] Example 2

[0058] 0.4994 g of copper sulfate pentahydrate, 0.5820 g of cobalt nitrate hexahydrate, 0.5816 g of nickel nitrate hexahydrate, 0.5950 g of zinc nitrate hexahydrate and 0.7464 g of aluminum nitrate hexahydrate were weighed respectively, and then transferred to an agate jar for ball milling for 20 min. After the mechanical mixing was completed, 0.632 g of ammonium bicarbonate was added and continued to ball mill for 30 min. The ball-milled mixture was then placed in a crucible and transferred to a muffle furnace and reacted at 700 ° C for 6 h. After the reaction was completed, it was cooled to room temperature to obtain a high entropy oxide, which was recorded as catalyst B.

[0059] Example 3

[0060] Weigh 0.3049 g of copper chloride dihydrate, 0.5820 g of cobalt nitrate hexahydrate, 0.5816 g of nickel nitrate hexahydrate, 0.5648 g of zinc sulfate heptahydrate and 0.3026 g of aluminum chloride monohydrate respectively, and then transfer them to an agate jar for ball milling for 20 min. After the mechanical mixing is completed, add 0.076 g of thiourea and continue ball milling for 30 min. Then place the ball-milled mixture in a crucible and transfer it to a muffle furnace and react at 1000 ° C for 2 h. After the reaction is completed, cool it to room temperature to obtain a high entropy oxide, which is recorded as catalyst C.

[0061] Example 4

[0062] 0.4832 g of copper nitrate hexahydrate, 0.3460 g of cobalt sulfate heptahydrate, 0.5816 g of nickel nitrate hexahydrate, 0.5950 g of zinc nitrate hexahydrate and 0.7464 g of aluminum nitrate hexahydrate were weighed respectively, and then transferred to an agate jar for ball milling for 20 min. After the mechanical mixing was completed, 0.42 g of urea was added and the ball milling was continued for 30 min. The ball-milled mixture was then placed in a crucible and transferred to a muffle furnace and reacted at 800 ° C for 4 h. After the reaction was completed, it was cooled to room temperature to obtain a high entropy oxide, which was recorded as catalyst D.

[0063] Comparative Example 1

[0064] 0.4832 g of copper nitrate hexahydrate, 0.5820 g of cobalt nitrate hexahydrate, 0.5816 g of nickel nitrate hexahydrate, 0.5950 g of zinc nitrate hexahydrate and 0.7464 g of aluminum nitrate hexahydrate were weighed respectively, and then transferred to an agate pot for ball milling for 20 min. The ball-milled mixture was then placed in a crucible and transferred to a muffle furnace and reacted at 900 ° C for 3 h. After the reaction was completed, it was cooled to room temperature to obtain a high entropy oxide, which was recorded as catalyst E.

[0065] Comparative Example 2

[0066] Weigh 0.4832g of copper nitrate hexahydrate, 0.5820g of cobalt nitrate hexahydrate, 0.5816g of nickel nitrate hexahydrate, 0.5950g of zinc nitrate hexahydrate and 0.7464g of aluminum nitrate hexahydrate in a 500mL beaker and add 100mL of deionized water and stir vigorously, which is recorded as solution A. Then prepare 100mL of sodium hydroxide solution (2M) in another 500mL beaker, which is recorded as solution B. Then, solution A is quickly and evenly added to solution B within 1min and stirred evenly for 60min. After the stirring is completed, age at room temperature for 12h, then filter the resulting slurry and wash it with deionized water until it is neutral. Finally, the obtained initial product is dried at 100℃ overnight and placed in a muffle furnace to react at 900℃ for 3h to obtain a high entropy oxide catalyst, which is recorded as catalyst F.

[0067] Analysis and test example 1

[0068] Figure 1 The XRD spectra of the Cu-based high entropy oxides prepared in Experimental Examples 2 and 3 show that both samples have sharp diffraction peaks, indicating that they have high crystallinity. After further attribution, it was found that the prepared high entropy oxides have a rock salt crystal structure, indicating that the high entropy oxides were successfully synthesized. In addition, the crystal structure of the prepared high entropy oxides will not be affected by the change of the modifier and the change of the chemical state of the metal salt, indicating the universality of this method.

[0069] Figure 2 The scanning electron microscope image of the Cu-based high entropy oxide prepared in Experimental Example 4 is shown in FIG. Figure 2 It can be seen that the prepared high entropy oxide presents regular polygons of different sizes and is spread evenly.

[0070] Figure 3 : are the He-TPD curves of Comparative Example 1 and Experimental Example 3. Figure 3 As shown, there are two obvious and two weak O2 desorption peaks on the surface of catalyst E. The peak temperatures of the obvious desorption peaks are located at around 336°C and 683°C, respectively, which are attributed to the surface and bulk lattice oxygen. The curve shows that catalyst E can only desorb lattice oxygen at a higher temperature. On the other hand, there is one obvious and one weak O2 desorption peak on the surface of catalyst C. The peak temperature of the obvious desorption peak is located at 103°C. Its broad peak indicates that it is composed of lattice oxygen and adsorbed oxygen. This result shows that the addition of modifiers is beneficial to the low-temperature activation of surface and bulk lattice oxygen, which is beneficial to the catalytic reaction.

[0071] The catalysts of the embodiments and comparative examples were applied to the CO2 hydrogenation activity test conditions: the catalyst loading was 0.2 g, the reaction temperature was 200°C to 550°C, and the CO2 / H2 (v / v=1:4) mixed gas flow rate was 40 mL / min.

[0072] The catalysts of each embodiment and comparative example were used in the stability test of CO2 hydrogenation reaction in the same device, and the test conditions were: catalyst loading amount was 0.2g, reaction temperature was 400℃, feed gas flow rate was 40mL / min, and long-term stability test time was 40h. The activity and stability results of the catalysts in the embodiments were expressed as CO2 conversion rate, and CO2 concentration was tested using online chromatography.

[0073] The catalyst is used in the CO2 hydrogenation reaction, and its performance evaluation formula is as follows:

[0074] CO2 conversion(%)=(CO2in–CO2out) / CO2in×100%

[0075] The measurement results are shown in the following table:

[0076] Table 1 CO2 conversion rate of high entropy oxide prepared in Examples 1-4 of the present invention and Comparative Examples 1 and 2 (%)

[0077]

[0078] In Examples 1 to 4, high entropy oxides prepared using modifiers, wherein catalyst A has excellent CO2 conversion rate. Although the conversion rate of CO2 is low at low temperature (200-300°C), it is higher than the catalysts prepared in other embodiments, especially the comparative catalysts. After further increasing the reaction temperature, the CO2 conversion rate has been significantly improved, reaching 39.4% at 400°C, and its CO2 conversion rate can reach 59.7% as the temperature further increases. In addition, after a stability test of up to 50h at 400°C, its conversion rate remains unchanged. Although the overall performance of the catalyst prepared in Examples 2-4 is slightly lower than that of catalyst A, it still has better catalytic performance and thermal stability. The catalysts prepared by conventional methods without adding modifiers not only have poor low temperature performance, but also poor high temperature performance and catalytic stability, which may be related to the lattice oxygen that is not fully exposed.

[0079] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A high entropy material, characterized in that: Including oxides of active metal elements and oxides of structurally stable metal elements; The active metal elements are copper, cobalt and nickel; The structural stabilizing metal elements are zinc and aluminum; The molar ratio of the active metal element to the structurally stable metal element is 6:4; The crystallinity of the high entropy material is 56.7% to 72.3%; The high entropy material is prepared by the following steps: Mechanically mixing a precursor containing an active metal element and a structurally stable metal element with a modifier, and subjecting the mixture to high temperature treatment to obtain the high entropy material; The specific steps of mechanical mixing include: after ball milling the active metal element precursor and the structurally stable metal element precursor for the first time, adding the modifier and performing a second ball milling; The modifier is selected from at least one of urea, ammonium bicarbonate or thiourea.

2. The high entropy material according to claim 1, characterized in that The first ball milling time is 15 to 30 minutes; The second ball milling time is 20 to 40 minutes.

3. The high entropy material according to claim 1, characterized in that: The active metal element precursor and the structurally stable metal element precursor are selected from at least one of nitrates, sulfates or chlorides of the corresponding metal elements; The molar ratio of each element in the active metal element precursor and the structurally stable metal element precursor is 1:1; The molar ratio of the total molar amount of the active metal element precursor and the structurally stable metal element precursor to the molar amount of the modifier is 0.5-2.

4. The high entropy material according to claim 1, characterized in that The temperature of the high temperature treatment is 700-1000°C; The high temperature treatment time is 2 to 6 hours.

5. A catalyst, characterized in that The catalyst comprises the high entropy material according to any one of claims 1 to 4.

6. A method for hydrogenating carbon dioxide, characterized in that: At least the following steps are included: The mixed gas containing carbon dioxide and hydrogen is contacted with a catalyst to react and obtain a product containing carbon monoxide, methane or methanol; The catalyst is selected from the catalyst according to claim 5.

7. The method according to claim 6, characterized in that In the mixed gas, the volume ratio of carbon dioxide to hydrogen is 4:1; The flow rate of the mixed gas is 20 mL / min to 50 mL / min; The mass of the catalyst is 0.2-0.5 g.

8. The method according to claim 6, characterized in that The reaction temperature is 200-550°C.

Citation Information

Patent Citations

  • Cu-Zn-based catalyst used in reverse water gas shift reaction, and preparation method and application thereof

    CN103230799A

  • Zn-Cu alloy catalyst and application thereof in in-situ hydrogenation of carbon dioxide

    CN109499579A